Revisiting kapwa Filipino ethics, subjectivity, and self-formation - Solitario, Jeizelle (2022)
In this article I trace the formation of what I call "Filipino servant subjectivity" by examining the Tagalog concept of kapwa (fellow being) in relation to colonialism, Christianity, and neoliberalism. I argue that although colonization is consequential to subject formation, self-formation based on culture is also consequential to Filipino servant subjectivity. Following Michel Foucault's theory on governmentality, I revisit monographs, ethnographies, and historical accounts to show how the concept of kapwa and kapwa ethics, along with institutional or colonial power, contribute to the formation of and resistance to servant subjectivity among Filipinos.
Keywords: Christianity; Neoliberalism; Imperialism